From in vitro development to accessible luminal interface of neonatal bovine-derived intestinal organoids - Gerald D. Dykstra; Minae Kawasaki; Claire R. Burbick; Craig S. McConnel; Yoko M. Ambrosini (BMC Veterinary Research)
Abstract Background Intestinal organoids provide physiologically relevant in vitro models that bridge the gap between conventional cell culture and animal studies. Although these systems have been developed for adult cattle, their use in neonatal calves—who are particularly vulnerable to enteric disease—has not been well established. Neonatal diarrhea remains a major health concern in modern agriculture, yet age-appropriate models for studying its pathogenesis are lacking. Given that host–pathogen interactions vary with developmental stage, there is a need for culture systems that reflect the distinct biology of the neonatal gut. In this study, we developed intestinal organoids and organoid-derived monolayers from 14-day-old dairy calves to enable research on early-life intestinal function and disease. Results Organoids were successfully established from five intestinal sections of 14-day-old dairy calves using customized growth media and characterized by immunofluorescence and gene expression analyses. They remained viable for over 300 days of cryopreservation and were serially passaged at least 15 times. Rectal organoid-derived monolayers were further assessed by electron microscopy and barrier function assays, demonstrating stable transepithelial electrical resistance and controlled paracellular permeability. Conclusions Optimized methods for adult bovine intestinal organoids and rectal organoid-derived monolayers are applicable to neonatal intestinal epithelial stem cells. Organoids cultured from 14-day-old calves captured key aspects of the multicellularity and functionality of the native epithelium. Future work should focus on adapting monolayer culture methods for additional gut regions, particularly the proximal gastrointestinal tract. Neonatal rectal monolayers represent a promising platform for advancing veterinary research, agricultural innovation, and studies of zoonotic disease.